2003
DOI: 10.1046/j.1440-1746.2003.03198.x
|View full text |Cite
|
Sign up to set email alerts
|

Rodent nutritional model of non‐alcoholic steatohepatitis: Species, strain and sex difference studies

Abstract: The Wistar strain and the male sex are associated with the greatest degree of steatosis in rats subjected to the MCD diet. Of the groups studied, male C57/BL6 mice develop the most inflammation and necrosis, lipid peroxidation, and ultrastructural injury, and best approximate the histological features of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
181
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(201 citation statements)
references
References 39 publications
(87 reference statements)
16
181
1
3
Order By: Relevance
“…Consequences are the disruption of membranes and the production of reactive metabolites such as MDA [20] . This study found high hepatic MDA levels in 100% fat-diet fed rats in accordance with studies by others [25][26][27][28] . Glutathione is the major intracellular non-protein antioxidant and plays a crucial role in the detoxification of free radicals [30,31] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequences are the disruption of membranes and the production of reactive metabolites such as MDA [20] . This study found high hepatic MDA levels in 100% fat-diet fed rats in accordance with studies by others [25][26][27][28] . Glutathione is the major intracellular non-protein antioxidant and plays a crucial role in the detoxification of free radicals [30,31] .…”
Section: Discussionsupporting
confidence: 93%
“…When the hepatocyte is injured, plasma membrane can be disrupted and the leakage through extracellular fluid of the enzyme occurs where they can be detected at abnormal levels in the serum [24] . AST and ALT activities have been found to be increased in NASH rats [10,[25][26][27][28] . In contrast, AST and ALT activities decreased significantly with 6 wk of 100% fat diet in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6 Therefore, a suitable animal model is required to reflect the natural course and etiological background of NASH in humans.…”
mentioning
confidence: 99%
“…Mice receiving a MCDD have lower fasting insulin and glucose levels and normal glucose tolerance, suggesting enhanced hepatic insulin sensitivity (17). However, MCDD also causes significant weight loss (18), and the relative influence of weight loss and liver fat accumulation has not been addressed. Moreover, in mice with steatohepatitis induced by MCDD, insulin receptor substrate phosphorylation in the liver was impaired, rather than enhanced, after a bolus of insulin administered into the portal vein (19), possibly because the inflammatory signals associated with hepatitis might confound effects on insulin sensitivity.…”
mentioning
confidence: 99%